Hyper IgE Syndrome in an Isolated Population in Israel - Lachover-Roth, Idit; Lagovsky, Irina; Shtorch-Asor, Atalia; Confino-Cohen, Ronit; Reinstein, Eyal; Garty, Ben-Zion (Frontiers in Immunology, 2022)
Introduction Hyper IgE syndromes (HIES) are a group of rare primary immunodeficiency characterized by high levels of serum IgE, cold abscesses, pulmonary infections, and eczema. ZNF341 deficiency was described in 2018 in 11 patients clinically diagnosed previously with HIES. Eight of those patients, all offspring of consanguineous couples, are from three families who live in a Muslim village in Israel which has approximately 15,000 residents. Objective Our study aimed to evaluate the prevalence of ZNF341 mutation in the population of the village. Methods Three hundred DNA samples of females were included in the study. The samples belong to females that were referred to the Meir Medical Center for prenatal genetic testing before pregnancy, during 2017-2019: 200 samples were from the village, and 100 samples of Muslim females were from other villages. All samples were tested by Sanger sequencing for the ZNF341 mutation (c.904C>T, NM_001282933.1). Results Heterozygous nonsense mutation in ZNF341 was found in ten samples (5%) of the study group compared to zero in the control group (p<0.01). Conclusion The carrier frequency of the mutation in ZNF341 in the studied village population is 1:20. This high frequency is probably due to founder mutation and consanguineous marriages.